Replication fork blocking deficiency leads to a reduction of rDNA copy number in budding yeast - Taichi Murai; Shuichi Yanagi; Yutaro Hori; Takehiko Kobayashi (iScience, 2024)
Summary: The ribosomal RNA genes are encoded as hundreds of tandem repeats, known as the rDNA, in eukaryotes. Maintaining these copies seems to be necessary, but copy number changes in an active manner have been reported in only frogs, flies, Neurospora, and yeast. In the best-studied system, yeast, a protein (Fob1) binds to the rDNA and unidirectionally blocks the replication fork. This block stimulates rDNA double-strand breaks (DSBs) leading to recombination and copy number change. To date, copy number maintenance and concerted evolution mediated by rDNA repeat turnover were the proposed benefits of Fob1-dependent replication fork arrest. In this study, we tested whether Fob1 provides these benefits and found that rDNA copy number decreases when FOB1 is deleted, suggesting that Fob1 is important for recovery from low copy number. We suppose that replication fork stalling at rDNA is necessary for recovering from rDNA copy number loss in other species as well.